Role of TNF-α-induced m6A RNA methylation in diseases: a comprehensive review - Wang, Youlin; Liu, Jing; Wang, Yongchen (Frontiers in Cell and Developmental Biology, 2023)
Tumor Necrosis Factor-alpha (TNF-α) is ubiquitous in the human body and plays a significant role in various physiological and pathological processes. However, TNF-α-induced diseases remain poorly understood with limited efficacy due to the intricate nature of their mechanisms. N6-methyladenosine (m6A) methylation, a prevalent type of epigenetic modification of mRNA, primarily occurs at the post-transcriptional level and is involved in intranuclear and extranuclear mRNA metabolism. Evidence suggests that m6A methylation participates in TNF-α-induced diseases and signaling pathways associated with TNF-α. This review summarizes the involvement of TNF-α and m6A methylation regulators in various diseases, investigates the impact of m6A methylation on TNF-α -induced diseases, and puts forth potential therapeutic targets for treating TNF-α-induced diseases.